2022
DOI: 10.1021/acs.nanolett.2c04091
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Autophagy and Blocking Autophagic Flux via a Virus-Mimicking Nanodrug for Cancer Therapy

Abstract: Maximizing the therapeutic capacity of drugs by allowing them to escape lysosomal degradation is a long-term challenge for nanodrug delivery. Japanese encephalitis virus (JEV) has evolved the ability to escape the endosomal region to avoid degradation of internal genetic material by lysosomes and further induce upregulation of cellular autophagy for the purpose of their mass reproduction. In this work, to exploit the lysosome escape and autophagy-inducing properties of JEV for cancer therapy, we constructed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…8). 119 This nanodrug comprised a JEV mimic virion decorated with anti-PDL1 antibodies and encapsulated with hydroxychloroquine (HCQ), an autophagy inhibitor widely used in clinical practice. In vivo studies have demonstrated that this nanodrug effectively upregulates cellular autophagy, inhibits autophagic flux, induces tumor cell apoptosis, and enhances immune response.…”
Section: Virus-mimicking Nanosystems For Biomedical Applicationsmentioning
confidence: 99%
“…8). 119 This nanodrug comprised a JEV mimic virion decorated with anti-PDL1 antibodies and encapsulated with hydroxychloroquine (HCQ), an autophagy inhibitor widely used in clinical practice. In vivo studies have demonstrated that this nanodrug effectively upregulates cellular autophagy, inhibits autophagic flux, induces tumor cell apoptosis, and enhances immune response.…”
Section: Virus-mimicking Nanosystems For Biomedical Applicationsmentioning
confidence: 99%
“…This is because LysoSensor probes rely on the decreased pH values to sense the endo-lysosomal compartments, and the protons that create a low pH environment are released into the cytoplasm upon the compartment rupture 36 , 37 . Moreover, LysoSensor probes exhibit a pH-dependent increase in fluorescence intensity and are almost non-fluorescent when outside acidic compartments 38 . Based on this, we studied the integrity of endo-lysosomal compartments by measuring the fluorescence intensity of LysoSensor Green.…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomal escape through JEV promoted the drug aggregation in tumors, inducing autophagy while inhibiting autophagolysosome by HCQ, which significantly enhanced the therapeutic effect on breast cancer. 192 …”
Section: Application Of Nanomedicine Combined With Autophagy Regulato...mentioning
confidence: 99%